Trade in International Maritime Services : How Much Does Policy Matter? - Fink, Carsten (Washington, DC: World Bank, 2014)
Maritime transport costs significantly impede international trade. This article examines why these costs are so high in some countries and quantifies the importance of two explanations: restrictive trade policies and private anticompetitive practices. It finds that both matter, but the latter have a greater impact. Trade liberalization and the breakup of private carrier agreements would lead to an average of one-third lower liner transport prices and to cost savings of up to US dollar 3 billion on goods carried to the United States alone. The policy implications are clear: there is a need not only for further liberalization of government policy but also for strengthened international disciplines on restrictive business practices. The authors propose an approach to developing such disciplines in the current round of services negotiations at the World Trade Organization (WTO).